(untitled) (Fiep Bulletin - online, 2014)
The osseous tissue has as characteristic the continuous cellular absorption and recomposition regulated by the interaction of RANKL and OPG. In case its continuity is lost, that is, any kind of bone injury, its remodeling leads to restoration and consequent skeletal integrity and its metabolism is influenced by hormonal, local, behavioral, environmental, and nutritional factors. The chronic consumption of alcohol may contribute to this imbalance, and, although significant correlations between the excessive alcohol intake and bone consolidation have been reported, new studies must be developed considering the great disparity between the time of exposure and quantity of alcohol intake comprising different protocols. The objective of this study was to verify quantitatively the effects of chronic alcohol consumption on bone healing and density on Wistar rats. The expression of OPG and RANKL was also observed. For this purpose, 30 Wistar rats were randomly divided into two groups: G1 (group 1) consisted of 15 rats which had, for 100 days, a liquid diet of liquor diluted in water with a progressive and controlled concentration; G2 (group 2) consisted in 15 rats on a liquid diet of only water and free of alcohol. After the 92nd day of the induction period of alcoholism, tibial defects of 3 mm in diameter were created in both groups and after 8 days from this surgery procedure the animals were euthanized and the tibiae were removed. The percentage of renovated bone and osseous density were submitted to histometric analysis. Through immunohistochemistry, the expression of OPG and RANKL were analyzed. As a result, it was verified that the osseous density and bone remodeling were smaller in the alcoholic group; it was also found a differentiation in the expression of OPG and RANKL. These results show that the proposed protocol of alcohol intake produces negative effects in the gain of bone quality when compared to the control group.